Professor Judi Wakhungu on turning national attention to climate change and food security - Wakhungu, Judi W. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Farmers in some areas are adapting to climate change, others are being "completely wiped out," pointing to the need for focused interventions. How are Kenyan farmers coping with shifting weather patterns?